Empirical model for forecast the Peruvian sea surface temperature - Matellini, Benjamin (2007)
In the present work an empirical model based on the warm water volume in the Equatorial Pacifi c Ocean is studied as a tool to forecast variations of sea surface temperature off the coast of Perú, which will be useful as a tool for giving early warnings of El Niño effects. The relation between the warm water volume and the depth of the 20°C isotherm is greater in the Central Pacifi c along latitude 0°. Several months later the changes of this volume affect the sea surface temperature off Perú particularly when its anomalies are positive. The model estimates the time when sea surface temperature begins to rise associated with El Niño effects in the coastal Niño 1 Region, the time when the event peaks, and the medium term trends.